Exploring research trends in sustainable mountain and rural tourism (SMRT): A bibliometric study with biblioshiny and VOSviewer - Vipan Kumar; Ashish Nag; Suman Sharma; Rohit Thakur; Ajay Bisht (Journal of Rural Tourism, 2026)
Purpose – This study aims to analyse the development and trends of sustainable mountain and rural tourism research from 1990 to 2025, with a focus on identifying key themes, influential contributors, and emerging directions in the literature.Methodology/Design/Approach – The study employs a bibliometric analysis of Scopus-indexed publications, utilizing tools such as VOSviewer and Biblioshiny to map research clusters, authorship patterns, and geographic distributions.Findings – The results indicate that countries such as China, Spain, United Kingdom, and Italy are leading contributors to the field. Key research themes include socioeconomic empowerment, gender dynamics, rural demographic change, and sustainable tourism development. The findings also highlight a growing emphasis on balancing economic growth with environmental conservation, driven by increasing demand for nature-based tourism linked to health awareness and urban stress.Originality/Value – This study provides a comprehensive synthesis of sustainable mountain and rural tourism research, offering insights into evolving academic trends and future research directions. It underscores the importance of integrating community participation, policy innovation, and environmental stewardship to support resilient economies, ecosystem sustainability, and cultural heritage preservation.